Experimental Investigation of Thermal Behavior of Cross Flow Plate-fin Heat Exchanger with Offset Strip Fin. (2016) - kuchhadiya, B.B.; Rathod, P.P.
Abstract: The Present work is carried out to investigate the thermal behavior of cross flow plate fin heat exchanger having offset strip fin. An experimental set up has been built in the laboratory to test the Plate fin Heat exchanger. Sets of experiments had conducted to determine the thermal performance of the given heat exchanger. Mass flow rate of cold fluid, mass flow rate of hot fluid, hot fluid inlet temperature, cold fluid inlet temperature, hot fluid and cold fluid inlet pressure are considered as input parameters. The values of the heat transfer co-efficient, effectiveness and pressure drops are obtained for the different value of the input parameters. The experimental results are compared with the correlations developed by Maiti and Sarangi, Manglik and Bergles and Joshi and Webb. Finally, based on the experimental results coluburn factor (j) correlation is developed to predict the value of heat transfer co-efficient.